Crystal market: a way to study knowledge-based dynamic capabilities. Issue 4 (19th May 2021) - Curado, Carla; Henriques, Paulo; Proença, Isabel; Maia, Diogo
Abstract : Purpose: In this work, the authors address a gap in the literature on the contribution of dynamic capabilities and internal contingencies to performance in a highly competitive environment. Design/methodology/approach: The authors use data from the Premier Football (soccer) League in Portugal over ten years. This league works as a laboratorial setting and enables the authors to identify the influences of the variables in the study. Findings: The authors find evidence that human capital is decisive to a team's performance. This study's findings question the role of the alignment between the different levels of the organization: strategic, tactical and operational. Research limitations/implications: With this work, the authors stress the importance (1) of using alternative scenarios in management research and (2) of the way that human and social capitals and managerial cognition and internal contingencies influence the development of knowledge-based dynamic capabilities, especially in highly regulated industries such has sports clubs. Practical implications: This work provides evidence on the importance of strategic coherence at different structural levels of the organization. Furthermore, it highlights the need to secure the right resources at the right time. Originality/value: The authors propose a setting to run the study: a crystal market and an original measure of performance that reflect the relative achievement of market potential.